Analisis Rantai Nilai dan Model Bisnis Ekonomi Kreatif pada Usaha Bengkel Las Pandawa Jaya - Veronika, Elsadai Ria; Tarigan, Jumay Eferta; Hanum, Sayidah Latifah; Dewi, Putri Kemala (Masyarakat Ekonomi Syariah Bogor, 2024)
The aim of this research is to analyze the strategies used by the creative industry, especially Bengkel Las Pandawa Jaya, in attracting consumer interest. This research presents how Bengkel Las Pandawa Jaya Business creates value chains and business models in their business. The results obtained through this research show that the owner focuses on adding value through good service to consumers. The business always strives to accept criticism and suggestions from consumers and focuses on the classic welding workshop methods.